Effect of Training Small Side Game on Attacking Skills in the Gorontalo City MAN 1 Futsal Team - Diuli, Mohamad Reza Pratama (Jurnal Ilmiah Mandala Education (JIME), 2025)
The Influence of Small Sided Games Training on Attacking Skills in the Futsal Team of MAN 1 Gorontalo City. Department of Physical Education, Health, and Recreation. State University of Gorontalo. The purpose of this study is to determine the influence of Small Sided Games training on futsal attacking skills. The research employs an experimental method with a sample of 10 futsal players from MAN 1 Gorontalo City, selected from a population of 30 players. Data collection was conducted using Game Situation tests and analyzed through descriptive and inferential statistical methods to test the research hypothesis. Based on the results of the t-test analysis on attacking skills, the t-observed value was -3112 with a significance value of 0.012 < 0.05, indicating that Small Sided Games training has a significant effect on futsal attacking skills. These results demonstrate that Small Sided Games training has a fairly significant impact on the attacking skills of the futsal team at MAN 1 Gorontalo City.